Ocular Insert: Dosage Form for Sustain Opthalmic Drug Delivery - Sunil Kumar Thakral; Badri P. Nagori; Roshan Issarani; Munish Ahuja (Indonesian Journal of Clinical Pharmacy, 2012)
Except for skin, the eye is the most easily accessible site for topical administration of a medication. Traditional topical ophthalmic formulations (eye drops and ointments) have poor bioavailability because of rapid pre-corneal elimination, conjunctival absorption, solution drainage by gravity, induced lacrimation and normal tear turnover. This leads to frequent  installations of concentrated medication to achieve a therapeutic effect. The typical “pulse-entry” type drug release observed with ocular aqueous solutions (eye drops), suspensions and ointments can be replaced by more controlled, sustained, and continuous drug delivery, using a controlled-release ocular drug delivery system. Ocular inserts are solid or semisolid sterile preparations, of appropriate size and shape, designed to be inserted behind the eyelid or held on the eye and to deliver drugs for topical or systemic  effect. These are polymeric systems into which the drug is incorporated as a solution or dispersion. They are better tolerated as to drainage and tear flow compared with other ophthalmic formulation and produce reliable drug release in the conjunctival cul-de-sac.Key words: Eye, ocular inserts, films simulated tear fluid, cul-de-sac Penyisipan Okular: Sediaan untuk Penghantaran Obat Mata DiperlambatAbstrakMata adalah organ yang paling mudah dijangkau untuk pengobatan topikal selain kulit. Formulasi sediaan topikal tradisional untuk mata (tetes mata dan salep) memiliki ketersediaan hayati yang rendah karena cepat dieliminasi sebelum mencapai kornea, absorpsi konjungtiva, kekeringan cairan mata karena gravitasi, lakrimasi terinduksi, dan pergantian normal air mata. Hal ini mengarahkan pada penggunaan obat yang pekat secara berulang untuk menghasilkan efek terapi. Tipe obat pulse-entry seperti tetes mata, suspensi, dan salep dapat digantikan dengan penghantaran obat yang lebih terkontrol, diperlambat, dan berkelanjutan menggunakan sistem penghantaran obat okular yang pengeluarannya dikontrol. Sediaan penyisipan okular merupakan sediaan steril berbentuk solid dan semisolid, dengan ukuran dan bentuk yang sesuai, serta didesain untuk dapat disisipkan di belakang kelopak mata atau diletakkan di atas mata untuk menghantarkan efek obat secara topikal atau sistemik. Sediaan ini  merupakan sistem polimer yang tidak larut atau terdispersi. Sediaan ini lebih baik dalam hal pengeringan dan aliran air mata dibandingkan formulasi sediaan mata yang lain dan menghasilkan pengeluaran obat yang reliabel pada konjungtiva kuldesak.Kata kunci: Mata, penyisipan okular, simulasi cairan air mata film, kuldesak